2006
DOI: 10.1158/0008-5472.can-05-2001
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Sphingosine-1-Phosphate Receptors by FTY720 Inhibits Angiogenesis and Tumor Vascularization

Abstract: FTY720, a potent immunomodulator, becomes phosphorylated in vivo (FTY-P) and interacts with sphingosine-1-phosphate (S1P) receptors. Recent studies showed that FTY-P affects vascular endothelial growth factor (VEGF)-induced vascular permeability, an important aspect of angiogenesis. We show here that FTY720 has antiangiogenic activity, potently abrogating VEGF-and S1P-induced angiogenesis in vivo in growth factor implant and corneal models. FTY720 administration tended to inhibit primary and significantly inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
222
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(244 citation statements)
references
References 30 publications
18
222
3
1
Order By: Relevance
“…FTY-720 has been shown to have direct antitumor effects (32,33). We initially confirmed that treatment with low doses of FTY-720 had no effect on tumor growth whilst retaining the capacity to reduce both circulating and tumor-infiltrating T-cell populations (Supplemental Fig.…”
Section: Both Tumor Resident and Infiltrating T-cells Contribute To Tmentioning
confidence: 53%
“…FTY-720 has been shown to have direct antitumor effects (32,33). We initially confirmed that treatment with low doses of FTY-720 had no effect on tumor growth whilst retaining the capacity to reduce both circulating and tumor-infiltrating T-cell populations (Supplemental Fig.…”
Section: Both Tumor Resident and Infiltrating T-cells Contribute To Tmentioning
confidence: 53%
“…3,27 In contrast, other studies have reported that FTY720 actually inhibits vascular endothelial growth factor-induced vascular permeability and angiogenesis. [28][29][30] The antiangiogenic effects of FTY720, though surprising based on its potent agonist activity, are proposed to occur as a result of functional antagonism. Although both S1P and FTY720 have been shown to internalize the S1P 1 receptor into the endosomal pathway, FTY720 induces ubiquitinylation and proteosomal degradation of the receptor.…”
mentioning
confidence: 99%
“…The S1P signaling system is involved in tumor neovascularization [50,51] . A recent report [52] has shown that repeated administration of monoclonal anti-S1P antibody inhibits tumor growth in several tumor models, including orthotopic injections of MDA MB-231 and MDA MB-468 breast carcinoma cells and SKOV3 ovarian cancer cells, and subcutaneous injection of A549 lung adenocarcinoma cells.…”
Section: Tumor Angiogenesismentioning
confidence: 99%